Experimental cross-section evaluation data for ⁷Be photoproduction by ¹²C, ¹⁴N, ¹⁶O nuclei in the energy range between 40…90 MeV - Dovbnya, A.N.; Deyev, O.S.; Kushnir, V.A.; Malyshevsky, V.S.; Malykhina, T.V.; Mitrochenko, V.V.; Perezhogin, S.A.; Torgovkin, A.V.; Fomin, G.V.; Shramenko, B.I. (Вопросы атомной науки и техники, 2013)
The ⁷Be isotope produced in the upper atmosphere under the action of cosmic radiation is an important factor in population radiation load. A correct determination of the radiation dose coming from this isotope calls for consideration of the photonuclear mechanism of ⁷Be production by the nuclei of oxygen and nitrogen. The paper gives the experimental yields from A(γ, X)⁷Be nuclear reactions in the bremsstrahlung beam versus the end-point energies of electrons (from 40 to 90 MeV). The mathematical model approach with the GEANT4 class library was used to calculate the spectra of bremsstrahlung incident on the targets. Based on the experimental results, we have calculated the A(γ, X)⁷Be reaction cross-sections for oxygen, nitrogen and carbon. Calculated values of photonuclear reaction cross-sections for ⁷Be production by ¹²C, ¹⁴N, ¹⁶O nuclei were obtained with the use of the TALYS package. Agreement between experimental and calculated results only for ¹²C and ¹⁴N is shown.